Disability and Poverty in Vietnam - Mont, Daniel; Cuon, Nguyen Viet (World Bank, 2013)
Disability is significantly correlated with poverty in Vietnam, according to data from the 2006 Vietnam Household Living Standards Survey, especially when the extra costs of living with a disability are taken into account. This disability-poverty link is also associated with lower educational attainment, an important factor in determining poverty and productive economic activity in general, both for household-based businesses and wage employment. Not taking into account these associations and the extra costs of disability will make some poor disabled people invisible in poverty statistics and impede efforts to reduce poverty.